2014
DOI: 10.1080/13102818.2014.974303
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic and cultural characteristic of strainLactobacillus gasseri4/13 of human origin

Abstract: Lactobacillus gasseri within the Lactobacillus acidophilus group is a major species in the human microflora. The potential probiotic properties of a L. gasseri strain of human origin were evaluated. Out of 17 studied L. gasseri strains, L. gasseri 4/13 showed the highest immunomodulatory effect (induction of interferon gamma measured by sandwich enzyme-linked immunosorbent assay) in Balb/c mouse splenocytes in vitro and the highest rate of adhesion to Caco-2 human epithelial cells. The strain also reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Strains of L. crispatus have been associated with the ability to exert competitive exclusion and antimicrobial against vaginal human pathogens [69e71], being proposed as potential vaginal probiotic [72]. On the other hand, some trains of L. gasseri and L. johnsonii have also shown probiotic characteristics such as immunomodulatory [73] and anti-infective [74e76].…”
Section: Discussionmentioning
confidence: 99%
“…Strains of L. crispatus have been associated with the ability to exert competitive exclusion and antimicrobial against vaginal human pathogens [69e71], being proposed as potential vaginal probiotic [72]. On the other hand, some trains of L. gasseri and L. johnsonii have also shown probiotic characteristics such as immunomodulatory [73] and anti-infective [74e76].…”
Section: Discussionmentioning
confidence: 99%
“…As a common strain in Sichuan pickle product, L. plantarum A3 also reveals great potential in probiotic yogurt in terms of bacterial population, texture and flavor [12]. Meanwhile, probiotic yogurt has many health benefits and can maintain a sufficient amount in the human gastrointestinal tract, such as milk fermented with probiotic strains such as Bifidobacteria and Lactobacilli [13,14]. Milk fermented with L. plantarum A3 in this research revealed a novel texture characteristic in terms of hardness, acidity and water holding capacity when combined with the traditional L. bulgaricus and S. thermophilus strains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, all types of milk from whole milk to fat-free milk contain the milk protein casein or its hydrolysis components (amino acids), which in the process of putrefaction are biotransformed into VOC and VSC. Consumption of fermented milk products containing live microorganisms with probiotic activity by Lactobacillus species has beneficial effects on the body (Baltova and Dimitrov 2014). By improving the balance of intestinal microflora and action against microbes which are responsible for the production of VSCs are limited (Iwamoto et al 2010).…”
Section: Medication and Substance-inducedmentioning
confidence: 99%
“…By improving the balance of intestinal microflora and action against microbes which are responsible for the production of VSCs are limited (Iwamoto et al 2010). Also unfavorable conditions such as low oral pH may decrease the beneficial effects (Porter 2011;Burton et al 2006;Aprea et al 2016;Baltova and Dimitrov 2014;Smith et al 2016;Venkateshwarlu et al 2004).…”
Section: Medication and Substance-inducedmentioning
confidence: 99%